Interaction Patterns and Verbal Development in a TPR-Based Preschool EFL Classroom: A Qualitative Case Study - Anggit Laesa Oktaviani; Devian Try Gustary; Gunawan (Journal of English Language Teaching, Literatures, Applied Linguistic (JELTLAL), 2026)
This study investigates the development of classroom interaction patterns and students’ verbal ability in a Total Physical Response (TPR)-based English classroom for young learners. Conducted as a qualitative case study at Excellent Academy (pre-school EFL classroom), the research involved eight students aged 4 to 6 years with diverse characteristics. Data was collected through classroom observations, field notes, interviews, and verbal coding rubric across six instructional meetings, and analyzed using thematic analysis. The findings reveal that interaction patterns initially followed a highly teacher- entered Initiation–Response–Feedback (IRF) structure, with students responding primarily through physical actions. Over time, interaction evolved into a more dynamic and participatory process, marked by the emergence of peer interaction and studentled activities, although the IRF framework remained dominant. In terms of verbal development, students demonstrated gradual progression from pre-verbal to emerging, developing, and advanced stages. This development was supported by repeated exposure, multimodal input, scaffolding, and opportunities for pushed output. The study supports key theoretical perspectives, including TPR, Krashen’s Input Hypothesis, Vygotsky’s Sociocultural Theory, and Swain’s Output Hypothesis, highlighting the importance of structured input and interactive learning environments in early language acquisition. Despite variations in learners’ backgrounds, all students showed improvement in verbal production. The findingssuggest that TPR is an effective approach for fostering both interaction and early language development in young learners,Although integrating more communicative strategies may further enhance peer interaction and language use.